Magnetoelasticity of Fe1-x Gax thin films on amorphous substrates - Ramírez, G. A. (2021)
In this work, we study the magnetoelastic behavior of Fe1−xGax (0.11 < x < 0.19) thin films, grown on glass and oxidized Si(100) amorphous substrates, that present an isotropic crystalline texture in the film plane. The magnetoelastic coupling coefficients are obtained through the cantilever deflection technique. We find that the magnetoelastic response is larger for samples grown on glass with respect to those grown on Si(100), and such a response increases for larger Ga concentrations for both substrates used. Furthermore, the increasing substrate temperature during growth does not appear to have a significant effect on magnetoelastic behavior of samples grown on Si(100). From a model that takes into account the elastic grain interaction for isotropic systems, we are able to describe the experimentally observed behavior. We find that the magnetoelastic response of the samples grown on glass are well described by the Voigt model, while the samples on Si(100) present an intermediate response between the Voigt and Reuss models.